A case of mammary sparganosis due to infection with Spirometra mansoni. Issue 4 (12th May 2019) - Zuo, Jun; Feng, Hai Gang; Xie, Sha Sha; Yang, Jun Tao
Abstract: The authors report the case of a 56‐year‐old woman with mammary sparganosis due to infection with a plerocercoid tapeworm larva of Spirometra mansoni . Magnetic resonance imaging revealed an area of heterogeneous density in outer upper quadrant of the right breast, with a high likelihood of malignancy. During surgery for the removal of a granuloma, the parasite was discovered and excised. The authors review the pathological and imaging features of mammary sparganosis.